Pengaruh Budaya Organisasi dan Kepemimpinan Transformasional Terhadap Kinerja Karyawan: Peran Mediator Motivasi Berprestasi - Sepna Sri Lestari; I Made Budiana (Pusat Riset dan Inovasi Nasional, 2025)
The purpose of this study is to explore the influence of organizational culture and transformational leadership on performance through the mediating variable of achievement motivation. The type of research used is explanatory research, while the approach used is a quantitative approach. The measurement tool used is a questionnaire with a Likert scale measurement consisting of four variables: employee performance, achievement motivation, organizational culture, and transformational leadership. Performance is a series of employee behaviors and actions related to the achievement of organizational goals. Achievement motivation is an individual's tendency to strive for success and have goal orientation, as well as measure activities based on successful or failed outcomes. Organizational culture is a habit that is continuously repeated and becomes a lifestyle for a group of individuals in the organization, which is then followed by new members. Transformational leadership is a leadership style where the leader works with the team to identify the need for change, create an inspirational vision, and execute the change with team commitment. The population in this study consists of 182 office and store staff employees of PT. Hokimart Indonesia, a retail company in Bekasi, West Java. The sampling technique used is total sampling, referring to the employee data owned by the company. The results show that organizational culture has a significant positive influence on employee performance, organizational culture has a significant positive influence on achievement motivation, transformational leadership has a significant positive influence on both employee performance and achievement motivation, and achievement motivation can mediate the relationship between organizational culture and transformational leadership on employee performance. These findings highlight the importance of the role of achievement motivation in mediating the relationship between organizational culture and transformational leadership to enhance employee performance.